Analysing effect of the factors on ultrasonic seam tensile properties of nonwoven fabrics by Nested Anova Design - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2015)
Purpose - The purpose of this paper is to investigate the factors effecting ultrasonic seam tensile properties. Design/methodology/approach - In this study, 100 percent polypropylene and 100 percent polyester spunbond and meltblown nonwoven fabrics were sewn by using ultrasonic sewing machine with different rollers which have two, three and four rows. Seam tensile properties of the sewn nonwoven fabrics were investigated. Four-Level Nested Anova Design was applied to the data by using Minitab 15 software program. Findings - Higher seam strength values were obtained by using four rows roller, PP fiber, spunbond fabric and 50 g/m(2) fabric area density for all nonwoven fabrics. Statistical significance was found between fabric area density, roller rows and seam tensile strength properties and between fabric type, roller rows and seam elongation at break values. Originality/value - When the authors look at the studies related to ultrasonic sewing, several researchers studied on welding parameters of ultrasonic sewing but very limited studies were performed on assembling of nonwoven fabrics with ultrasonic sewing. Therefore effect of production methods of nonwoven fabrics on the properties of ultrasonic sewing such as seam strength and elongation at break should be investigated.
Keywords: Mechanical properties; Polyester; Nested Anova Design; Nonwoven fabric; Polypropylene; Ultrasonic sewing; ENERGY; POLYESTER; COTTON